Sex Offender Reintegration: Consequences of the Local Neighborhood Context - Burchfield, Keri B. (American journal of criminal justice, 2014)
In this paper we seek to assess the effects of the neighborhood context on sex offenders’ perceptions of their neighbor’s willingness to support them upon release. We also examine the effect of the neighborhood context on sex offenders’ feelings of stress and the need for secrecy, potential risk factors for recidivism. Using survey data obtained from a sample of 333 in-treatment sex offenders, we find that the neighborhood social context exerts an important influence on sex offenders’ perceptions of neighborhood support. We also find that offenders are less likely to worry about the negative repercussions of their status as a sex offender when they perceive higher levels of neighborhood support. Despite the limitations of the sample, implications of this research indicate a need for policies that promote public awareness of local sex offenders while also offering education and understanding about potential barriers to successful sex offender reintegration.